Factors affecting complementary and alternative medicine (CAM) use by adult diabetic patients: A systematic review using the theoretical domains framework (TDF) - Alzahrani, Abdulaziz Saud; Greenfield, Sheila M.; Paudyal, Vibhu (Research in social and administrative pharmacy, 2022)
It is estimated that approximately 50% of patients with diabetes use some form of complementary and alternative medicine (CAM) to manage their condition. The objective of this study was to undertake a systematic review to explore factors that influence the use of CAM by diabetic patients. A systematic review of literature was conducted using Cochrane and PRISMA guidelines. Nine databases including MEDLINE and EMBASE were searched from 2010 to March 2021 using medical subject headings and natural language keywords. Data in relation to factors associated with use of CAM in diabetic patients 18 years of age and older were extracted and further categorised as per the theoretical domains framework (TDF). Forty-three studies from 28 countries were included. A total of 84 factors were identified. Key factors related to the ‘intentions (to treat and relieve symptoms) and goals’ domain of the TDF. Accessibility and affordability compared to physician visits and modern medicines (TDF- environmental context and resources), ‘Social influences’ from family members, friends, religious and spiritual scholars were amongst other factors reported to be important. Users also reported lack of trust in modern medicines and perceived CAMs to be safer and free from adverse effects. Decisions to use CAM in diabetes are multifactorial. Healthcare professionals' awareness of patients' CAM use and associated factors can inform counselling practices and promote treatment optimisation, adherence and patient safety through avoidance of drug-CAM interactions. Alleviating patients’ concerns and reluctance to use prescribed treatments are imperative to achieve therapeutic goals. Improving access and affordability is imperative where high costs prevent use of prescribed medicines leading to many patients using CAM as a standalone therapy. [Systematic review registration: PROSPERO CRD42019125036]. •Healthcare professionals' awareness of diabetic patients' CAM use and associated factors can inform effective counselling and communication practices during clinical consultations.•Addressing patient fears, concerns about prescribed treatments which can be important factors in regards to patient use of CAM can enable promotion of treatment optimisation and adherence to prescribed treatments.•By expecting diabetic patients might use CAM, healthcare professionals could help to minimise any possible interactions between CAM and other medications.•Improving access and affordability is imperative where high costs of prescribed treatments prevent their use leading patients to resort to CAM as a standalone therapy.